The Case for Angioplasty in Patients with Symptomatic Intracranial Atherosclerosis - McTaggart, Ryan A.; Marks, Michael P. (Frontiers in Neurology, 2014)
Intracranial atherosclerotic disease (ICAD) is likely the most common cause of stroke worldwide and remains highly morbid even with highly monitored medical therapy. Recent results of the SAMMPRIS trial, which randomized patients to stenting plus aggressive medical management versus aggressive medical management alone have shown that additional treatment of intracranial atherosclerotic lesions with the Wingspan stent is inferior to aggressive medical management alone. In light of these results, there has been renewed interest in angioplasty alone to treat symptomatic ICAD. This article will briefly review the natural history of ICAD and discuss the possible future for endovascular treatment of ICAD with primary intracranial angioplasty in appropriately selected patients.